Tax Planning, Income Tax Expenses, and Banking Equity - Riyans Ardiansyah; Roni Padliansyah; Rudy Bin Ansar; Lim Ming Fook (Vifada Management and Social Sciences, 2025)
Purpose: This study aims to analyze the effect of Tax Planning and Income Tax Expenses on the equity of banking companies listed on the Indonesia Stock Exchange for the period 2019–2023. The focus of this study is to examine the extent to which taxation strategies can influence a company's capital structure, particularly its equity component. Research Design and Methodology: This study employs a quantitative, causal-comparative design. The population in this study comprises all companies in the banking sub-sector, and the sample was selected using purposive sampling, yielding 8 companies that met specific criteria. The data used are secondary, obtained from annual financial reports. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²), all conducted in SPSS version 27. Findings and Discussion: The analysis results show that Tax Planning and Income Tax Expenses have a positive and significant effect on Equity, both partially and simultaneously. This proves that optimal management of taxation aspects can increase the equity value of banking companies. Implications: The practical implications of this study indicate that companies need to integrate tax-planning strategies and income-tax expense management into their long-term financial policies to strengthen their capital position and increase their attractiveness to investors.